MUSRENBANG: COLLABORATION BETWEEN VILLAGE GOVERNMENT AND STAKEHOLDERS TO OPTIMIZE VILLAGE DEVELOPMENT - Hindratma, Deffy May; Suryati, Iis; Hendrawan, Ruli; Khumayah, Siti; Wulandari, Sri (Ridwan Institute, 2024)
Regional Development is a National Priority (PN) in 2024 which aims to reduce inequality and ensure equity. One of the important stages in regional development is the Village Development Planning Conference (Musrenbang) which aims to prepare a development plan in a but-up and participatory manner by involving various stakeholders in the village. The purpose of this study is to analyze the collaboration between the Village Government and stakeholders in the Village Musrenbang by referring to the collaboration framework from Thomson and Perry. This study uses a qualitative method with data collection techniques from observation, interviews and documentation. The results of the study show that collaboration between the Village Government and stakeholders in the Village in Kuningan Regency is optimal in all dimensions of collaboration presented by Thompson and Perry. Other findings from the study show that collaboration in planning can increase public trust in the Government and can encourage innovation in Village Development. The things that are lacking in the implementation of the Village Musrenbang in Kuningan Regency are the absence of special regulations from the Regional Government related to collaboration between the Village Government and stakeholders, there is still egocentric between the Executive and the Legislature regarding the proposed activities to be realized and the problem of budget limitations to accommodate all proposals in the Regional Revenue and Expenditure Budget (APBD).